Oracle database 12c release 2 real application cluster handbook : concepts, administration, tuning and troubleshooting - Gopalakrishnan, K. (Kandhasamy), 1976-; Alapati, Sam R. (McGraw-Hill Education, 2018)
This comprehensive guide has been fully updated to cover the latest features and tools of Oracle Real Application Clusters 12 c Through clear instruction and detailed examples, Oracle Database 12 c Real Application Clusters Handbook: Concepts, Administration, Tuning and Troubleshooting teaches how to build, configure, and maintain a dynamic enterprise computing infrastructure. This thoroughly revised edition covers best uses for the latest tools and features-all from the practical standpoint of a working DBA. You will discover how to prepare hardware, configure the software, optimize data integrity, and integrate seamless failover protection. Brand-new flex and large cluster technologies are explained in full detail, and readers will get complete solutions for securing data and continuing business operations in the event of hardware failure. Presents all the new information needed to effectively use Oracle Real Application Clusters 12 c -considered the most radical overhaul ever Offers detailed coverage of troubleshooting, performance tuning, and application development.